Efficiency performance and cost structure of Portuguese energy "utilities" – Non-parametric and parametric analysis. (15th July 2018) - Rita, Rui; Marques, Vitor; Lúcia Costa, Ana; Matos Chaves, Inês; Gomes, Joana; Paulino, Paulo
Abstract: The analysis of regulated companies' performance in the natural gas and electricity sectors requires a deep knowledge of these companies' efficiency performance and cost structure. First, this research paper presents a study based on a sample of natural gas distribution portuguese companies (DSO). This study analyzes how efficient these companies are. To evaluate the companies' efficiency, this study employed both parametric and non-parametric methodologies, such as panel data regression, and Data Envelopment Analysis (DEA). Second, this research paper seeks to understand the cost structure of two samples of companies (DSO and retailers). To reach this aim two different types of analysis were carried out. One such analysis relied on a parametric methodology, which involved estimating a data panel regression. This second analysis entailed evaluating data related to the companies' cost structures which was obtained through a questionnaire previously circulated to retailers and last resort suppliers. Results obtained through such analysis suggest that fixed costs tend to represent one third of total operating costs. Regarding retailers, results show that the number of clients is the main cost inductor and that fixed costs represent, on average, from 21% to 34%, depending on whether they are regulated and on the sector they operate. Hlighlights: Recognition of 4 homogenous efficiency groups within gas distribution companies. Supply points and volume of gas are relevant cost inductors of distribution sector. In the distribution fixed costs represents about one third of total operating costs. For Retailers and last resort supplier fixed costs presents a range from 21% to 34%. Regulated retailers/last resort supplier tend to have a lower share of fixed costs.